MULTI-OBJECTIVE OPTIMIZATION OF POWER GENERATION EXPANSION IN WEST AND SOUTH SULAWESI POWER SYSTEM - Mahyuddin, Astuty (Department of Electrical Engineering, University of Patria Artha, 2017)
In 2013, most of electricity demand of South and West Sulawesi Power System was fulfilled by fossil fuel power plants. The use of fossil fuel not only leads to high operational cost, but also emits high amount of carbon. To control carbon emission Kyoto Protocol and Peraturan Presiden emphasize that the generation expansion has to consider the environmental aspect and economic aspect. In order to obtain an efficient plan with low carbon emission, this research conduct multi-objective optimization of power generation expansion in South and West Sulawesi power system. The optimization was conducted by combining Particle Swarm Optimization (PSO) method and Analytic Hierarchy Process (AHP). The optimization in this research was consisted of cost and carbon emission function. Cost function itself was divided into three items. The items are capital cost of power plant, operation and maintenance cost, and investment cost of transmission line. To obtain the investment of transmission line, transmission expansion plant considering power losses (TEP) was performed first. The aim of TEP is to determine which transmission line should be added into the power system. The result of simulation and priority analysis shows that A6 is an efficient power plant expansion planning that fulfill environmental and economic aspect. Planning A6 is consisted of PLTA (996 MW), PLTMG (71 MW), PLTU (34 MW) and PLTGU (737 MW). Investment cost of transmission line, operational cost of power plant and investment cost of new power plant are Rp351.000.000.000, Rp4.000.000.000, and Rp.60.596.000.000.000 respectively. The accumulation of carbon emission for 5 periods by applying plan A6 is 651 tons.